Current practices and challenges in the management of cancer-associated thrombosis: a survey of Italian oncologists - Antonuzzo, Andrea; Ermacora, Paola; Lanzetta, Gaetano; Lucchesi, Maurizio; Platania, Marco; Bossi, Paolo (Frontiers in Oncology, 2025)
PurposeThis study investigates current practices and challenges in managing cancer-associated thrombosis (CAT) among Italian oncologists, with the objective of evaluating adherence to guidelines for primary thromboprophylaxis, treatment approaches, and safety considerations. Additionally, it aims to identify areas for potential improvement in clinical decision-making and standardization of CAT management.MethodsA cross-sectional survey was conducted between February and June 2024 among Italian oncologists, facilitated by the Italian Network for Supportive Care in Oncology (NICSO). The online survey comprised 16 multiple-choice questions that addressed primary thromboprophylaxis practices, thrombosis treatment, and anticoagulation safety concerns.ResultsA total of 75 oncologists, evenly distributed across the Italian territory, participated in the survey. Among them, 48% consistently administered primary thromboprophylaxis, with a higher prevalence observed in cases of pancreatic (64%) and lung cancers (12%). Overall, 61% utilized risk assessment models (RAMs), mainly the Khorana score. Drug preference varied, with 89% favoring low-molecular-weight heparin (LMWH) for thromboprophylaxis. For established thrombosis, 72% preferred LMWH, administering treatment to 52% of patients for 3 to 6 months. Awareness of drug-drug interactions was high (93%), and 83% expressed concerns about bleeding risks, with renal impairment identified as a significant comorbidity.ConclusionThe survey highlights variability in CAT management, with limited use of RAMs and personalized treatment plans. These findings underscore the need for enhanced clinician education and standardized guidelines to optimize CAT management, including strategies to address bleeding risk and improve the safety of anticoagulation therapy.